2011
DOI: 10.1029/2010jf001722
|View full text |Cite
|
Sign up to set email alerts
|

Direct measurement of channel erosion by debris flows, Illgraben, Switzerland

Abstract: [1] The timing and magnitude of channel bed erosion by three debris flows was measured in 2008 at the Illgraben catchment, Switzerland, using a scour sensor which consisted of a vertical array of erodible sensor elements. During the largest debris flow, sediment was entrained progressively and stepwise at the flow head within 20 s after front arrival, and onset of erosion started before maximum values for flow height and normal and shear stress, measured nearby, were reached. Erosion in one of the two smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
263
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(284 citation statements)
references
References 33 publications
20
263
1
Order By: Relevance
“…Without such information, it is not possible to unambiguously attribute scouring and filling phases to specific flow conditions. However, other field (Berger et al, 2011b) and experimental evidences (Mangeney et al, 2010) identify that the maximum scouring is related to the passage of the debris-flow front.…”
Section: Discussionmentioning
confidence: 99%
“…Without such information, it is not possible to unambiguously attribute scouring and filling phases to specific flow conditions. However, other field (Berger et al, 2011b) and experimental evidences (Mangeney et al, 2010) identify that the maximum scouring is related to the passage of the debris-flow front.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its high degree of debris-flow activity, this catchment became one of the most studied debris flow sites in the Alps. During the last decade, studies focused on various aspects of the debris flow process addressing the flow process itself (Hürli-mann et al, 2003;McArdell et al, 2007), developing a reliable warning system for debris flows based on flow detection (Badoux et al, 2009), studying sediment transfer (Berger et al, 2010b;Bennet et al, 2012Bennet et al, , 2013 and the erosion process (Berger et al, 2010a(Berger et al, , b, 2011Schürch et al, 2011a, b;Bennet et al, 2014). Today, the channel is equipped with several measurement installations which allow estimation of typical flow parameters such as front velocity and flow depth.…”
Section: The Entrainment Model Development Site: Illgraben Catchmentmentioning
confidence: 99%
“…They concluded that the fragmentation of material from a matrix (gravel bed or bedrock) depends on the exposure of the particle to the basal forces acting on the matrix, and furthermore that the removal of sediment increases with increasing water content. To assess the timing and the absolute erosion depth caused by natural debris flows at the Illgraben channel, Berger et al (2010aBerger et al ( , 2011 installed a novel channel bed erosion sensor based on the concept of an electrical resistance chain. McCoy et al (2013) recently studied basal forces generated by erosive debris flows in Chalk Cliff catchment, Denver, Colorado USA, using a similar type of instrumentation consisting of erosion sensors similar to those in the Illgraben as well as erosion bolts in bedrock and a small force plate.…”
Section: F Frank Et Al: the Importance Of Entrainment And Bulking Omentioning
confidence: 99%
See 2 more Smart Citations